Novos complexos β-dicetonatos de európio com n-(piridin-2-il)amidas e n-(pirimidin-2-il)amidas como ligantes auxiliares: propriedades fotofísicas e modelagem estrutural teórica - Lima, Geórgia Batista Vieira de (2019)
Eighteen new Eu3+ ion complexes and their Gd3+ analogues with 1,3-diketonate as main ligands and N-(pyridine-2-yl)amides or N-(pyrimidine-2-yl)amides as ancillary ligands were synthesized and their specific properties investigated. The replacement of water molecules by those amides in the Eu3+ ion complexes increase the intrinsic quantum yields of luminescence, making them comparable or even more efficient than Eu3+ complexes with the well-known ancillary ligand 2,2’-bipyridine. Luminescence intrinsic quantum yield values range from 9.3% to 59.7%. The luminescence spectra of Gd3+ ion complexes in comparison with those of Eu3+ ones show that efficient ligand-to-metal intramolecular energy transfer processes take place. In most cases the experimental Judd-Ofelt intensity parameters (Ω2 and Ω4) for the Eu3+ ion complexes show variations as a function of the temperature (77 and 300 K) that overall apparently does not follow clearly any trend. For this reason, geometric variations (on the azimuthal angle ϕ and ancillary ligands distances) were carried out in the coordination polyhedron for simulating thermally induced structural changes. It has been observed that, in this way, the Ω2 and Ω4 can be satisfactorily reproduced by “in silico” experiments. It was concluded that, at low-temperature, the ancillary ligands become closer to the Eu3+ ion and the angular variations affect more Ωଶ than Ωସ, in agreement to the theoretical calculations.